Flexible PAN / P25 porous nanotube film as well as preparation method and application thereof

The flexible PAN/P25 porous nanotube membrane was prepared by electrospinning method and P25 was exposed through solvent heat-induced reaction, which solved the problem of time-consuming and difficult recovery of existing photocatalytic oxidation technologies, and achieved efficient photocatalytic degradation and sterilization effects.

CN119771493APending Publication Date: 2025-04-08WUHAN POLYTECHNIC UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411744653.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-01
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing photocatalytic oxidation technology has problems such as long time consumption, difficulty in recycling and may cause secondary environmental pollution in water purification.

Method used

A flexible PAN/P25 porous nanotube membrane was prepared by electrospinning method, and some components were removed through the thermally induced reaction of ethylene glycol solvent to expose more P25 and improve photocatalytic activity.

Benefits of technology

Efficient photocatalytic degradation and sterilization have been achieved, and the performance of photocatalytic degradation of RhB has been improved by 4 times. The performance remains basically unchanged after 5 recycled use, and the inactivation rate of E. coli is as high as 95.8%, showing excellent economic, environmentally friendly and safe performance in water pollution treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771493A_ABST
    Figure CN119771493A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photocatalyst degradation of water pollution, and discloses a flexible PAN / P25 porous nanotube membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: ultrasonically dispersing TiO2 in N, N-dimethylformamide, sequentially adding polyacrylonitrile and polyvinylpyrrolidone, and magnetically stirring to obtain a uniform spinning solution; the spinning solution is subjected to electrostatic spinning and drying treatment, and a PAN / PVP / P25 nanofiber membrane is obtained; and cutting the PAN / PVP / P25 nanofiber membrane according to a preset size, transferring the cut PAN / PVP / P25 nanofiber membrane into a high-pressure reaction kettle, adding ethylene glycol, carrying out a solvothermal induction reaction, repeatedly washing with deionized water, and drying to obtain the flexible PAN / P25 porous nanotube membrane. The flexible PAN / P25 porous nanotube membrane is an economical, environment-friendly and safe sewage treatment material, is high in photocatalytic efficiency and low in cost, and is applied to treatment of water pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalyst degradation of water pollution and sterilization, and in particular to a flexible PAN / P25 porous nanotube membrane and a preparation method and application thereof. Background Art

[0002] The random discharge of organic pollutants and the growth of bacteria caused by eutrophication of water bodies have caused serious water pollution. Photocatalytic oxidation technology driven by solar energy has a wide range of applications in water purification. At the same time, the use of multifunctional powder materials to treat water pollution is also an efficient water purification technology. However, these methods are time-consuming and difficult to recycle, which will cause secondary pollution to the environment. Therefore, it is necessary to provide an economical, environmentally friendly and safe sewage treatment material to solve the above problems.

[0003] Electrospinning technology has become one of the main ways to effectively prepare nanofiber membranes with its advantages of simple manufacturing equipment, low cost, a wide variety of spinnable materials, and controllable process. It can well solve the problem of difficult recycling of nanofiber membranes; polyacrylonitrile (PAN) is widely used as a precursor of nanocarbon fiber because of its low cost, good spinning performance, and high carbonization rate; TiO2 nanophotocatalyst (P25) is widely used in the removal of organic pollutants, inactivation of harmful bacteria, and generation of clean energy due to its high stability, low cost, and eco-friendly, and has the characteristics of energy saving, green, high efficiency, sustainability, and low cost. Therefore, this application prepares a flexible PAN / P25 porous nanotube membrane by electrospinning and using PAN and P25, which is used in treating water pollution. Summary of the invention

[0004] Based on the above, the purpose of the present invention is to provide a flexible PAN / P25 porous nanotube membrane and its preparation method and application, which has high photocatalytic efficiency and low cost and is used in treating water pollution.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a flexible PAN / P25 porous nanotube membrane comprises the following steps:

[0007] Ultrasonic dispersion of TiO2 (P25) in N,N-dimethylformamide (DMF), sequential addition of polyacrylonitrile (PAN) and polyvinylpyrrolidone (PVP), and magnetic stirring to obtain a uniform spinning solution; electrospinning the spinning solution, and drying to obtain a PAN / PVP / P25 nanofiber membrane;

[0008] The PAN / PVP / P25 nanofiber membrane was cut into a preset size, transferred to a high-pressure reactor, ethylene glycol was added, a solvent thermal induction reaction was carried out, and then the membrane was repeatedly washed with deionized water and dried to obtain a flexible PAN / P25 porous nanotube membrane.

[0009] As a preferred embodiment of the method for preparing a flexible PAN / P25 porous nanotube membrane, the mass ratio of the PAN to the PVP is 1:1, the concentration of the PAN in the DMF is 1 g / mL, and the concentration of the P25 relative to the DMF is 0.01 to 0.04 g / mL.

[0010] As a preferred embodiment of the method for preparing a flexible PAN / P25 porous nanotube membrane, the concentration of the PAN relative to the ethylene glycol is 0.3 g / mL.

[0011] As a preferred solution for the preparation of a flexible PAN / P25 porous nanotube membrane, during the electrospinning process, a collecting device is used to collect the electrospinning product, the spinning temperature is 20-30°C, the relative humidity is 40-50%, and a 11-13 kV DC high voltage is connected.

[0012] As a preferred solution for the preparation method of a flexible PAN / P25 porous nanotube membrane, in the drying process after electrospinning, the drying temperature is 50 to 70° C. and the drying time is 1 to 3 hours.

[0013] As a preferred solution of the method for preparing a flexible PAN / P25 porous nanotube membrane, during the solvent thermal induction reaction, the reaction temperature is 170 to 190° C. and the reaction time is 2 to 4 hours.

[0014] A flexible PAN / P25 porous nanotube membrane is prepared by any of the preparation methods described above.

[0015] The invention discloses an application of a flexible PAN / P25 porous nanotube membrane. Based on the flexible PAN / P25 porous nanotube membrane, the flexible PAN / P25 porous nanotube membrane is applied in photocatalytic degradation and photocatalytic sterilization.

[0016] The beneficial effects of the present invention are:

[0017] The present invention provides a flexible PAN / P25 porous nanotube membrane and a preparation method and application thereof. Functional nanoparticles P25 are introduced into nanofibers by electrostatic spinning technology to prepare P25 / PAN / PVP nanofiber membranes. In order to achieve the purpose of pore formation and exposure of internal P25, ethylene glycol (EG) solvent thermal induction and phase separation are used to selectively remove PVP components and expose more P25 on the fiber tube surface, and finally prepare P25 / PAN porous nanotube membranes, which are economical, environmentally friendly and safe sewage treatment materials. When the amount of P25 added is 0.2g and the EG solvent thermal treatment time is 3h, the performance of photocatalytic degradation of RhB by PAN / P25-3 after ethylene glycol solvent thermal reaction is compared with PAN / PVP / P25-0.2, and the material performance remains basically unchanged after being recycled for 5 times. At the same time, the material also has excellent photocatalytic sterilization ability. After irradiation with monochromatic light with a wavelength of 365nm for 3h, the inactivation rate of Escherichia coli is as high as 95.8%, and it is effectively applied in the field of water pollutant treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.

[0019] Figure 1 are (A) FT-IR and (B) XRD spectra of (a) PAN / PVP, (b) PAN / PVP / P25-0.2, and (c) PAN / P25-3;

[0020] Figure 2 The SEM images and diameter distribution of the reaction products before and after the addition of P25 and the EG solvent thermal treatment: (A1-A4) PAN / PVP; (B1-B4) PAN / PVP / P25-0.2; (C1-C4) PAN / P25-3;

[0021] Figure 3 are the SEM images of the reaction products with different solvent thermal treatment times: (A1, A2) PAN / PVP / P25-0.2; (B1, B2) PAN / P25-2; (C1, C2) PAN / P25-3; (D1, D2) PAN / P25-4;

[0022] Figure 4 These are TEM images of PAN / P25-3 at different magnifications;

[0023] Figure 5are (A) N2 adsorption-desorption isotherms and (B) pore size distribution curves, (a) PAN / PVP-0.2, (b) PAN / P25-3;

[0024] Figure 6 The contact angle diagrams of different materials with water: (A) PAN / PVP; (B) PAN / PVP / P25-0.2; (C) PAN / P25-3;

[0025] Figure 7 Thermogravimetric curves: (a) PAN / PVP; (b) PAN / PVP / P25-0.2; (c) PAN / P25-3;

[0026] Figure 8 (A) DRS spectrum; (B) (αhν) 2 Relationship diagram with energy (hν); (C) PL spectra, (a) PAN / PVP / P25-0.2, (b) PAN / P25-3;

[0027] Fig. 9 (A) EIS Nyquist plot and (B) it transient response curve, (a) PAN / PVP / P25-0.2, (b) PAN / P25-3;

[0028] Fig.10 (A, C) degradation curves of RhB aqueous solution by different photocatalysts under simulated sunlight, (B, D) kinetic curves, (E) recycling performance of PAN / P25-3, (F) XRD spectra of PAN / P25-3 before and after use; (a) PAN / PVP / P25-0.1, (b) PAN / PVP / P25-0.15, (c, e) PAN / PVP / P25-0.2, (d) PAN / PVP / P25-0.25, (f) PAN / P25-2, (g) PAN / P25-3, (h) PAN / P25-4;

[0029] Fig.11 The three-dimensional fluorescence images of PAN / P25-3 degradation of RhB at different times: (A) -30 min, (B) 0 min, (C) 60 min, and (D) 150 min;

[0030] Fig.12 It is the active free radical capture experiment of PAN / P25-3 photocatalytic degradation of RhB;

[0031] Fig.13The photocatalytic inactivation performance of PAN / P25-3 for E. coli, (A) E. coli inactivation curve under different conditions, (B) sterilization rate bar graph, (C) optical image of E. coli colonies (dilution factor is 5000); (a) only PAN / P25-3 was added under dark conditions, (b) only light with a wavelength of 365 nm was irradiated, and (c) PAN / P25-3 was added under light with a wavelength of 365 nm. DETAILED DESCRIPTION

[0032] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.

[0033] This embodiment provides a method for preparing a flexible PAN / P25 porous nanotube membrane, comprising the following steps:

[0034] S100, ultrasonically dispersing TiO2 (P25) in N,N-dimethylformamide (DMF), sequentially adding polyacrylonitrile (PAN) and polyvinyl pyrrolidone (PVP), electrospinning the spinning solution, and drying to obtain a PAN / PVP / P25 nanofiber membrane;

[0035] Specifically, the mass ratio of PAN to PVP is 1:1, the concentration of PAN in DMF is 1 g / mL, and the concentration of P25 relative to DMF is 0.01 to 0.04 g / mL. Among them, the Mw of polyvinyl pyrrolidone is preferably 1,300,000, and the Mw of polyacrylonitrile is preferably 150,000.

[0036] Specifically, during the electrospinning process, a collecting device is used to collect the electrospinning product, the collecting device is placed 15 to 20 cm away from the needle tip of the syringe, the spinning temperature is 20 to 30° C., the relative humidity is 40 to 50%, and a 11 to 13 kV DC high voltage is connected. During the post-electrospinning drying process, the drying temperature is 50 to 70° C., and the drying time is 1 to 3 hours.

[0037] S200, cutting the PAN / PVP / P25 nanofiber membrane into a preset size, transferring it to a high-pressure reactor, adding ethylene glycol to react at high temperature, cooling it to room temperature, repeatedly washing it with deionized water, and freeze-drying it to obtain a PAN / P25 porous nanotube membrane.

[0038] Specifically, the concentration of PAN relative to ethylene glycol was 0.3 g / mL.

[0039] Specifically, when reacting in a high-pressure reactor, the reaction temperature is 170-190° C. and the reaction time is 2-4 hours.

[0040] The present invention will be further described below by means of specific examples.

[0041] Example 1

[0042] 0.2g P25 was ultrasonically dispersed in 6mL DMF, and 0.6g PAN and 0.6g PVP were added in sequence. After magnetic stirring for 6h, a uniform spinning solution was obtained. The spinning solution was transferred to a syringe with a steel needle for electrospinning. The electrospinning conditions were as follows: 12kV DC high voltage was connected, the receiver was placed 15cm away from the tip of the steel needle, the temperature was 25℃, and the relative humidity was 45%. The obtained material was placed in an oven at 60℃ for 2h to remove the residual solvent, and finally a PAN / PVP / P25 nanofiber membrane was obtained, named PAN / PVP / P25-0.2.

[0043] PAN / PVP / P25-0.2 was cut into appropriate sizes and transferred to a stainless steel high-pressure reactor. An appropriate amount of EG was added and the mixture was solvothermally reacted at 180 °C for 3 h. After cooling to room temperature, the membrane was repeatedly washed with deionized water and freeze-dried for 12 h to obtain a PAN / P25 porous nanotube membrane named PAN / P25-3.

[0044] Example 2

[0045] The preparation process and reaction conditions were basically the same as those in Example 1, wherein 0.1 g of P25 was added for reaction, and the obtained PAN / PVP / P25 nanofiber membrane was named PAN / PVP / P25-0.1.

[0046] Example 3

[0047] The preparation process and reaction conditions were basically the same as those in Example 1, wherein 0.15 g of P25 was added for reaction, and the obtained PAN / PVP / P25 nanofiber membrane was named PAN / PVP / P25-0.15.

[0048] Example 4

[0049] The preparation process and reaction conditions were basically the same as those in Example 1, wherein 0.25 g of P25 was added for reaction, and the obtained PAN / PVP / P25 nanofiber membrane was named PAN / PVP / P25-0.25.

[0050] Example 5

[0051] The preparation process and reaction conditions were basically the same as those in Example 1, wherein the solvent thermal reaction time was 2 h, and a PAN / P25 porous nanotube membrane was obtained, which was named PAN / P25-2.

[0052] Example 6

[0053] The preparation process and reaction conditions were basically the same as those in Example 1, wherein the solvent thermal reaction time was 2 h, and a PAN / P25 porous nanotube membrane was obtained, which was named PAN / P25-4.

[0054] In order to further illustrate the key points of this patent, a comparative case is added for illustration.

[0055] Comparative Example 1

[0056] The preparation process and reaction conditions were basically the same as those in Example 1, wherein gP25 was not added to the reaction to obtain a PAN / PVP nanotube membrane.

[0057] The product preparation formulas of the above examples and comparative examples are shown in Table 1.

[0058] Table 1 Product preparation formulas of different embodiments and comparative examples

[0059]

[0060]

[0061] In order to further study the photocatalytic performance of the PAN / P25 porous nanotube film prepared in the present application, photocatalytic experiments were carried out on the products prepared in the above examples and comparative examples.

[0062] 1. Photocatalytic degradation of RhB

[0063] The photocatalytic performance of different materials was evaluated using a xenon lamp as a light source to simulate sunlight and a 10 mg / L RhB aqueous solution as a pollutant model. First, 50 mg PAN / PVP / P25-0.2 was added to 50 mL RhB solution, and the dark reaction was carried out for 30 minutes to reach the adsorption-desorption equilibrium state and an appropriate amount of supernatant was taken. Then, the xenon lamp light source was turned on for irradiation. An appropriate amount of supernatant was taken at regular intervals to measure its absorbance at 554 nm, and the change in RhB concentration was calculated to measure the photocatalytic performance of the material. Following the same operation, keeping the equivalent of P25 consistent, other materials of corresponding mass were added.

[0064] 2. Photocatalytic inactivation of E.coli

[0065] The concentration was 3×10 6CFU / mL of E.coli suspension. A DT365 filter was added to the xenon light source to filter the light source, and 10 mg of PAN / P25-3 was immersed in 10 mL of E.coli suspension. According to the same operation as in the photocatalytic degradation of RhB experiment, 500 μL of bacterial suspension was taken at regular intervals and diluted a certain multiple with sterile saline. The density of live bacteria was determined by the coating method: 100 μL of the dilution was coated on the LB solid culture medium, and the number of live bacteria was determined after constant temperature culture at 37°C for 12 hours to calculate the concentration change. At the same time, control experiments were performed under the conditions of only light and only adding PAN / P25-3 to measure the photocatalytic inactivation of E.coil by PAN / P25-3. Each group of experiments was repeated three times.

[0066] In addition, in order to further analyze the reaction mechanism and product performance, relevant performance analysis was also performed on the products prepared in the examples and comparative examples of the present application.

[0067] 1. Component and structure analysis

[0068] In order to explore the changes in the chemical composition of the above-mentioned composite materials, Fourier infrared spectrometer and X-ray diffractometer were used for analysis and characterization. Figure 1 (A) is the FT-IR spectrum. In curve a, 3400cm -1 The broad absorption peak near 3000-2900cm is attributed to the stretching vibration of -OH, which is due to the adsorption of moisture in the air on the surface of the sample; -1 and 1454cm -1 The absorption bands are due to the stretching and bending vibrations of CH; 2245cm -1 The C≡N stretching vibration at 1680cm -1 There is an obvious peak at 1450cm -1 and 1250cm -1 The peaks observed near are caused by C=C and CN stretching vibrations. Compared with curve a, curves b and c have a peak at 850-550 cm -1 A new broad peak appears at 1680cm-1, which belongs to the Ti-O-Ti stretching vibration peak, proving the existence of P25. -1 The relative intensity of the peak at was significantly weakened, indicating that PVP was largely removed after EG solvent thermal treatment.

[0069] Figure 1(B) is the XRD spectrum. There is no obvious diffraction peak in curve a, and in curve b, the characteristic peaks corresponding to the anatase phase in P25 and the characteristic peaks corresponding to the rutile phase in P25 appear, respectively, confirming the presence of P25 in the composite film, but the peak intensity is weak, which may be due to the fact that a large amount of P25 is wrapped inside the fiber, and the content of P25 exposed on the surface is small. The peak intensity of curve c increases significantly, which is due to the exposure of more P25 after EG solvent thermal treatment.

[0070] 2. Surface morphology analysis

[0071] Scanning electron microscopy was used to observe the changes in fiber surface morphology. Figure 2 As shown in (A1-A4), the surface of PAN / PVP fiber is smooth and the fiber diameter is 0.32μm. After adding P25, the fiber surface becomes rough and the fiber diameter increases to 0.72μm ( Figure 2 (B1-B4)), which may be due to the increased viscosity of the spinning solution making it difficult for the electrostatic force to stretch the fiber more thoroughly or the increased fiber diameter due to the load of P25 on the fiber surface and inside, e.g. Figure 2 As shown in (C1-C4), after 3h of EG solvent thermal treatment, the fiber swelled and the diameter increased to 0.9μm, and P25 inside the fiber was exposed. At the same time, it was found that the material had a special porous structure. For the formation of the structure, the following results were obtained: PAN and PVP are insoluble, and there is a phase separation phenomenon. Due to the different viscosities of the two, fibers with PAN as the main component on the outside and PVP as the main component on the inside were formed during the spinning process. Since PVP can be dissolved in EG, it is removed from the inside during the solvent thermal reaction to form a porous structure. In addition, since PAN is rich in a large amount of -CN and has the ability to coordinate with metal ions, P25 is still preserved on the fiber. This special structure will bring the following benefits: on the one hand, the porous structure can increase the specific surface area of ​​the material and provide more active sites; on the other hand, the porous structure is conducive to the entry of light and realizes multiple reflections and scattering on the inner wall of the fiber to improve the light collection and utilization efficiency, thereby producing stronger light response performance. Therefore, the above two aspects will be conducive to the improvement of photocatalytic performance.

[0072] The surface morphology of the material was observed by scanning electron microscopy as the solvent thermal treatment time changed. Figure 3 As shown in (A1, A2), only a small amount of P25 nanoparticles were loaded on the fiber surface, and most of them were probably encapsulated inside the fiber. After EG solvent thermal treatment for 2 h ( Figure 3(B1,B2)), due to the removal of part of PVP, pores are generated on the fiber surface, but nanotube structures are not formed and the internal P25 exposure is not obvious, and the highest light energy utilization rate still cannot be achieved. With the extension of the solvent heat treatment time, the pores on the fiber surface gradually increase, the number of exposed P25 nanoparticles increases, and the fiber forms a hollow tubular structure. However, too long a time (4 h) will lead to the aggregation of P25 nanoparticles ( Figure 3 (D2)), excessive aggregation will lead to a reduction in the contact area between P25 and pollutants, and the aggregation of P25 particles blocks the pores and closes the channel for light to enter the inner wall, which may affect the photocatalytic performance.

[0073] 3. TEM analysis

[0074] Figure 4 The TEM images shown further confirm the porous hollow tubular structure of PAN / P25-3. The exposed P25 nanoparticles are located on the fiber surface. The increase in pores and the exposure of P25 are both beneficial to increasing the specific surface area, providing more active sites, and facilitating the contact between organic dyes or bacteria in sewage and the catalyst. In addition, the light inside the tube wall can be refracted multiple times, improving the light utilization rate, which has a certain effect on enhancing the photocatalytic efficiency.

[0075] 4. Specific surface area analysis

[0076] The physical properties of the materials were further understood by measuring the N2 adsorption-desorption isotherms and pore size distributions of PAN / PVP / P25-0.2 and PAN / P25-3. As Figure 5 shown, the PAN / PVP / P25-0.2 fiber membrane presents a type III isotherm, indicating that the material is a non-porous or macroporous material, and the measured pore data are attributed to the voids generated by the interlaced stacking between fibers. PAN / P25-3 shows a combination of type III isotherm and H3-type hysteresis loop (0.8 < P / P0 < 1.0). The hysteresis loop is one of the main characteristics of mesoporous materials, indicating that the EG solvent heat treatment creates mesoporous channels in the material. The pore size distributions of the above two materials are relatively narrow (2 - 20 nm). The specific data are shown in Table 2. The specific surface areas of PAN / PVP / P25-0.2 and PAN / P25-3 are 12.29 m 2 ·g -1 and 25.74 m 2 ·g -1 ; the latter has an average pore size (increased from 15.33 nm to 24.76 nm) and pore volume (increased from 0.05 cm 3 ·g -1 to 0.16 cm 3 ·g -1) increases significantly, because the solvothermal reaction removes a large amount of PVP and generates a large number of pores, which leads to the increase of specific surface area, average pore size and pore volume.

[0077] Table 2 Physical properties of photocatalysts

[0078]

[0079] 5. Contact angle analysis

[0080] like Figure 6 As shown in the figure, the surface wettability of PAN / PVP, PAN / PVP / P25-0.2 and PAN / P25-3 was evaluated by testing the contact angle between the material surface and water. Due to the hydrophilicity of PVP, the PAN / PVP fiber membrane showed good hydrophilicity with a contact angle of only 21.3°. After loading P25, although the fiber surface became rough, it still showed good hydrophilicity ( Figure 6 (B)), which is due to the large amount of -OH on the surface of TiO2. After removing PVP, the contact angle of PAN / P25-3 slightly increased to 35.4°, but it still showed hydrophilicity. This may be due to the introduction of some hydrophilic groups such as -OH from EG on the surface of PAN / P25-3 during the solvothermal process. The material can still maintain hydrophilicity, which is beneficial to the treatment of pollutants in water.

[0081] 6. Thermogravimetric analysis

[0082] In order to investigate the changes in the content of material components, PAN / PVP, PAN / PVP / P25 and PAN / P25-3 were characterized by thermogravimetric analysis. Figure 7As shown. For PAN / PVP (curve a), when the temperature reaches 500°C, both components have completely volatilized. Observing curve b, due to the hydrophilicity of PVP, the membrane surface adsorbs moisture in the air, so between 25°C and 100°C, 3.41% of the mass loss is attributed to the moisture on the surface of the example. The mass loss between 100°C and 260°C is 0.7%, which is due to the presence of a small amount of DMF residue. PVP begins to pyrolyze at 260°C, and the mass loss rate is relatively slow at the beginning because part of PVP will cross-link with PAN. When the temperature rises to 280°C, PAN begins to pyrolyze, resulting in an increase in the mass loss rate. Therefore, between 260°C and 320°C, 38.41% of the weight loss can be attributed to the partial decomposition of PVP and the loss of a small amount of ammonia and hydrogen cyanide during the cyclization of PAN. Continuing to increase the temperature, PAN begins to lose weight for the second time due to carbonization decomposition, but the weight loss is slower than the previous time, which is due to PAN's better heat resistance. When the temperature rises to 600°C, all carbon is decomposed, leaving only P25 nanoparticles, and the residual weight percentage is 14.20%, which is close to the theoretical value (14.29%). In curve c, due to the removal of PVP, the amount of water adsorbed on the surface is small, so there is almost no mass loss before 100°C. The subsequent pyrolysis curve has a similar trend to curve a, and the final residual P25 content percentage (24.59%) is very close to the theoretical value (25%). The above results show that the EG solvothermal method can effectively remove the PVP component without causing the P25 nanoparticles to fall off the fiber.

[0083] 7. Optical absorption analysis

[0084] The light absorption behavior of PAN / PVP / P25-0.2 and PAN / P25-3 was studied by UV-Vis diffuse reflectance spectroscopy. Figure 8 (A) As shown. The absorption edges of PAN / PVP / P25-0.2 and PAN / P25-3 are 387nm and 391nm, respectively, which are attributed to the intrinsic band gap absorption of P25. PAN / P25-3 exhibits a higher light absorption value because the porous structure is conducive to the entry of light into the inner wall, and the tubular structure is conducive to multiple reflections of light on the inner wall, resulting in a higher light absorption value. At the same time, EG solvent thermal treatment may introduce functional groups such as -OH or -CHO into the material surface, which may be another reason for the increase in light absorption value. The obtained DRS spectrum is converted into g ) n / 2 Converted into Tauc diagram ( Figure 8 (B)), where α, h, v, a, E g They represent the absorption coefficient, Planck constant, optical frequency, direct transition constant and band gap energy respectively. The value of n depends on the type of optical transition of the semiconductor (n direct =1,n indirect=4), and extending the straight line part of the graph to the horizontal axis (y=0) yields the band gap energies (3.20 eV and 3.17 eV). The band gap energies of the two examples do not change significantly, indicating that P25 remains stable after solvothermal treatment.

[0085] As we all know, photogenerated electrons (e - ) and holes (h + ) is one of the important parameters that determine the photocatalytic activity. The PL spectrum of the example was detected under the excitation light of wavelength 200nm ( Figure 8 (C)) for comparative analysis - and h + It can be seen that the peak intensity of PAN / P25-3 near 420nm is significantly lower than that of PAN / PVP / P25-0.2, indicating that the recombination rate of photogenerated carriers is lower and the separation efficiency is higher. The reason may be that the porous structure shortens the e - and h + diffusion paths, thereby reducing the recombination rate.

[0086] 8. Photoelectrochemical properties

[0087] Fig. 9 The photoelectrochemical properties of the material are demonstrated. The arc radius of PAN / P25-3 is smaller, indicating that it has less resistance to free charge migration and a faster charge transfer rate. Faster charge transfer is beneficial to promote the separation efficiency of photogenerated carriers, thereby improving the photocatalytic efficiency. In addition, compared with PAN / PVP / P25-0.2, the photocurrent intensity of PAN / P25-3 is also increased, further confirming the e - -h + effective separation.

[0088] 9. Photocatalytic degradation of RhB performance

[0089] The performance of the obtained examples was studied by photocatalytic degradation of organic dye solutions, and RhB was selected as the research model. Fig. 9 To simulate the photocatalytic degradation curves and kinetic fitting of RhB aqueous solution by different photocatalysts under sunlight. As can be seen from the figure, all examples have a degradation effect on RhB, and the degradation characteristics conform to pseudo-first-order kinetics. The performance of materials that have not been thermally treated with EG solvent is not much different. This may be because the content of P25 nanoparticles on the surface is similar at this time, and most of them are wrapped inside the fiber. After EG solvent thermal treatment, the catalytic efficiency of PAN / P25-3 is much higher than that of PAN / PVP / P25-0.2. This is because EG solvent thermal treatment exposes more P25 nanoparticles. The larger the rate constant k, the stronger the catalytic performance of the photocatalyst. The catalytic rate of PAN / P25-3 (0.0240min -1) is PAN / PVP / P25-0.2(0.006min -1 ) by 4 times. This is because the porous fiber membrane PAN / P25-3 has a larger specific surface area, higher light absorption rate, and lower e - -h + Recombination rate, smaller impedance and stronger photocurrent.

[0090] In order to verify the stability of PAN / P25-3, the PAN / P25-3 used in the experiment was washed with anhydrous ethanol and deionized water and then tested again according to the above process, and a total of 5 sets of cycle test results were obtained. Fig.10 (E) shows the cyclic photocatalytic performance of PAN / P25-3. At the fifth cycle, PAN / P25-3 can still maintain about 94% of its original performance. In addition, XRD results ( Fig.10 (F)) shows that PAN / P25-3 has almost no change before and after use, which indicates that PAN / P25-3 has relatively excellent stability.

[0091] 10. Photocatalytic process and mechanism analysis

[0092] The degradation process of RhB was studied using a three-dimensional fluorescence instrument. Fig.11 As shown in (A), the two fluorescence characteristic peaks of the RhB solution with an initial concentration of 10 mg / L are: (a) Ex / Em = 550-575 / 620-660nm and (b) Ex / Em = 225-275 / 575-650nm; they are attributed to the rigid planar structure of RhB. The three-dimensional fluorescence spectrum after adsorption equilibrium is shown in Fig.11 (B) The shape, position and intensity of the characteristic fluorescence peaks hardly changed, indicating that the RhB molecules did not decompose during this process, but were only partially adsorbed by PAN / P25-3. As the photocatalytic reaction proceeded to 60 min ( Fig.11 (C)), the position of the fluorescence characteristic peak red-shifted, which is due to the N-deethylation reaction of the RhB molecule and the removal of some specific functional groups such as amine, hydroxyl and carbonyl to form a relatively small molecule. When the illumination time is extended to 150min ( Fig.11 (D)), the fluorescence intensity of the solution almost disappeared completely, indicating that the intermediates formed may be further decomposed into small molecules. Therefore, the main process of RhB degradation is speculated to be the dissociation of the conjugated chromophore structure of the RhB molecule and the mineralization of the corresponding intermediates.

[0093] In order to further understand the photocatalytic mechanism of PAN / P25-3, triethanolamine (TEOA), p-benzoquinone (p-BQ) and isopropyl alcohol (IPA) were used as photogenerated holes (h + ), superoxide radicals (·O2 -) and hydroxyl radical (·OH) scavengers. Fig.12 As shown in the figure, after adding the three free radical scavengers, the catalytic ability of PAN / P25-3 decreased to varying degrees. Among them, after adding TEOA, the catalytic ability of PAN / P25-3 decreased most significantly, indicating that + is the main active free radical. In the presence of IPA and p-BQ, the catalytic ability of RhB PAN / P25-3 decreased slightly, indicating that ·OH and ·O 2- It is a secondary active free radical.

[0094] 11. Photocatalytic sterilization performance

[0095] The photocatalytic sterilization performance of PAN / P25-3 under 365 nm light irradiation was studied using E. coli as a model (each experiment was repeated 3 times). Fig.13 As shown, under dark conditions, the number of surviving E. coli did not decrease significantly after 3 hours, indicating that the material itself is non-toxic and harmless to E. coli, but has a weak adsorption capacity. When only under light conditions, the bacterial concentration only decreased by 0.1 log within 3 hours. This is because the light band will cause the bacteria to produce oxygen free radicals, causing oxidative stress and leading to bacterial death, but the inactivation effect is still weak. When PAN / P25-3 was added under light conditions, the inactivation rate of E. coli was significantly improved, and the killing rate of E. coli reached more than 95%, which was significantly higher than the sum of the inactivation rates when only PAN / P25-3 was added and under light conditions alone. This shows that the synergistic effect of PAN / P25-3 and light irradiation plays an important role: under light conditions, PAN / P25-3 can produce different active free radicals, such as h + , e - , ·O 2- etc., where h + and e - It can trigger redox reactions and both can be converted into hydroxyl radicals, which can quickly attack and seize hydrogen atoms on viral or bacterial proteins or envelopes, thereby inducing them to lose their normal physiological functions and leading to death. 2- The attack on bacteria can cause the decrease of activity of some antioxidant enzymes (catalase, superoxide dismutase) of bacteria and damage of cell membrane, leading to gradual oxidative damage and leakage of intracellular substances, especially proteins and DNA, and finally leading to the death of bacteria and achieving the inactivation effect.

[0096] In summary:

[0097] A series of P25 / PAN / PVP composite fiber membranes were prepared by electrospinning, and PAN / P25 photocatalysts with porous structures were prepared by removing PVP through EG solvent thermal induction strategy. When the amount of P25 added was 0.2g and the EG solvent thermal treatment time was 3h, the best example PAN / P25-3 obtained had a 4-fold improvement in the performance of photocatalytic degradation of RhB compared with PAN / PVP / P25-0.2, and the material performance remained basically unchanged after being recycled 5 times. At the same time, the material also has excellent photocatalytic sterilization ability. After irradiation with monochromatic light of wavelength 365nm for 3h, the inactivation rate of Escherichia coli was as high as 95.8%.

[0098] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for preparing a flexible PAN / P25 porous nanotube membrane, characterized in that: The following steps are involved: Ultrasonic dispersion of TiO2 in N,N-dimethylformamide, sequential addition of polyacrylonitrile and polyvinyl pyrrolidone, and magnetic stirring to obtain a uniform spinning solution; electrostatic spinning of the spinning solution, and drying treatment to obtain a PAN / PVP / P25 nanofiber membrane; The PAN / PVP / P25 nanofiber membrane was cut into a preset size, transferred to a high-pressure reactor, ethylene glycol was added, a solvent thermal induction reaction was carried out, and then the membrane was repeatedly washed with deionized water and dried to obtain a flexible PAN / P25 porous nanotube membrane.

2. The method for preparing the flexible PAN / P25 porous nanotube membrane according to claim 1, characterized in that: The mass ratio of the PAN to the PVP is 1:1, the concentration of the PAN in the DMF is 1 g / mL, and the concentration of the P25 relative to the DMF is 0.01-0.04 g / mL.

3. The method for preparing the flexible PAN / P25 porous nanotube membrane according to claim 1, characterized in that: The concentration of PAN relative to the ethylene glycol was 0.3 g / mL.

4. The method for preparing the flexible PAN / P25 porous nanotube membrane according to claim 1, characterized in that: During the electrostatic spinning process, a collecting device is used to collect the electrostatic spinning product, the spinning temperature is 20-30° C., the relative humidity is 40-50%, and a 11-13 kV DC high voltage is connected.

5. The method for preparing the flexible PAN / P25 porous nanotube membrane according to claim 1, characterized in that: During the drying process after electrospinning, the drying temperature is 50-70° C. and the drying time is 1-3 hours.

6. The method for preparing the flexible PAN / P25 porous nanotube membrane according to claim 1, characterized in that: During the solvent thermal induction reaction, the reaction temperature is 170-190° C. and the reaction time is 2-4 hours.

7. A flexible PAN / P25 porous nanotube membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.

8. Application of a flexible PAN / P25 porous nanotube membrane, characterized in that: The flexible PAN / P25 porous nanotube membrane described in claim 7 is used in photocatalytic degradation and photocatalytic sterilization.

Citation Information

Patent Citations

  • Multifunctional air purification filter screen

    CN107469614A

  • Porous supported electrospun nano photocatalytic fiber membrane and preparation method thereof

    CN108842304A